Assessment of a support garment in parastomal bulging from a patient perspective: a qualitative study - Trine Borglit; Marianne Krogsgaard; Stine Zeberg Theisen; Mette Juel Rothmann (International Journal of Qualitative Studies on Health & Well-Being, 2022)
Aim To investigate patients’ experiences of the assessment of support garments in relation to a parastomal bulge. Methods We conducted a qualitative study with semi-structured interviews preceded by field observations. The 11 in-dept interviews were analysed using interpretative phenomenological analysis. Results In the assessment process patients lacked information from professionals on the advantages, disadvantages as well as criteria for choosing between garments. Garments had to fit patients’ needs and personal preferences; being comfortable, flexible and user-friendly. The garment created new possibilities and challenges; well-assessed garments reduced symptoms while poorly assessed worsened or induced symptoms and ended up unworn. When comorbidities were not accounted for, garments were unmanageable to patients. Patients needed guidance on how to apply and use the garment. Lack of hands-on-guidance left patients confused and helpless with unworn garments. Re-assessment of a garment before it could be worn was time consuming, stressful and required patients’ physical and mental resources. Conclusion Exploring patients’ expectations, symptoms, needs and comorbidity was vital for patients’ subsequent use and benefit of garments. Tailor-made information, hands-on-guidance and professional assistance are important in the assessment process. Interventions to support a patient centred, individual and systematic approach is warranted.